Methods for Setting Road Vehicle Movement Trajectories - Vesna Dragčević; Željko Korlaet; Ivica Stančerić (The Baltic Journal of Road and Bridge Engineering)
The paper gives overview of the methods for setting the vehicle movement trajectory. Results have been shown, within wider research project, of the comparative analysis of methods for setting vehicle movement trajectory, bearing in mind relevant criteria and respecting the results of proving range test drives on field. Respecting the laws of geometry of movement and behaviour of the vehicle under real traffic conditions in small radii curves, optimum shaping of steering path and defining of kinematic vehicle model was tested by using computer programme of verified reliability developed in the Faculty of Civil Engineering of the University of Zagreb.